The Innocents Abroad: International Students, Title IX, and the Need to Address Campus Safety - Thomas, James; Krsmanovic, Masha; Foster, Holly (Journal of International Students, 2024)
Expectations of campus safety and security are inherent in the development of policies internal to the campus environment as well as to national regulations inclusive of Title IX, the Clery Act, and so forth. Yet, there seems to be an ongoing concern that international students may have heightened risk or are less likely to report violations of policies and regulations. This research is focused on determining to what extent awareness of policies and regulations often linked to equality on campus are a part of international student orientations and outreach. By examining the timing, manner, and extent of training, this article seeks to add to the study of ways that campuses may better engage, prepare, and serve students engaged in international education experiences.